BUNGA PINJAMAN BAITUL TAMWIL MUHAMMADIYAH RASAU JAYA PERSPEKTIF FATWA MAJELIS TARJIH MUHAMMADIYAH TENTANG BUNGA KOPERASI - Satyananda Wicaksana; Rusdi Sulaiman; Nur Hakimah (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2025)
This research aims to find out how loan interest is implemented at Baitul Tamwil Muhammadiyah Rasau Jaya and to find out clearly whether the implementation of loan interest at Baitul Tamwil Muhammadiyah Rasau Jaya can be adjusted to the fatwa of the Muhammadiyah Tarjih Council regarding cooperative interest. Researchers use normative and empirical research types. Normative research functions to explore the fatwa of the Muhammadiyah Tarjih assembly regarding cooperative interest, while empirical research is to examine whether the implementation of loan interest at Baitul Tamwil Muhammadiyah Rasau Jaya can be adjusted to the fatwa of the Muhammadiyah Tarjih regarding cooperative interest. The data used in this research is primary data obtained from interviews with the management and customers of Baitul Tamwil Muhammadiyah Rasau Jaya and secondary data obtained from library sources such as books and journals. In this study, documentation, interviews, and observation were the methods used to collect data. Meanwhile, the researcher's data analysis techniques involved data reduction, data presentation, and conclusions. Then the validity of the data is tested through triangulation of technique, source, and time. The research results show that: 1) Baitul Tamwil Muhammadiyah Rasau Jaya applies loan interest. The interest (additional fees) will be returned to Baitul Tamwil members in the form of a loan. This is done based on the principle of ta'awun; 2) Based on its articles of association, Baitul Tamwil Muhammadiyah Rasau Jaya is declared a sharia savings and loan cooperative, thus it can be adjusted to the fatwa of the Muhammadiyah Tarjih Council regarding cooperatives.